2021
DOI: 10.5194/tc-2021-232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolving GIA in response to modern and future ice loss at marine grounding lines in West Antarctica

Abstract: Abstract. Accurate glacial isostatic adjustment (GIA) modeling in the cryosphere is required for interpreting satellite, geophysical and geological records and to assess the feedbacks of Earth deformation and sea level change on marine ice-sheet grounding lines. Assessing GIA in areas of active ice loss in West Antarctica is particularly challenging because the ice is underlain by laterally varying mantle viscosities that are up to several orders of magnitude lower than the global average, leading to a faster … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Two 3-D mantle viscosity structures, which were first constructed in Wan et al (2022), are built upon two different 1-D reference viscosity profiles:-the first model we referred to as EM3D_L, is characterized by a uniform viscosity of 𝐴𝐴 10 20 Pa s in the upper mantle (from the bottom of the lithosphere to the depth of 670 km), and a viscosity value of 𝐴𝐴 5 × 10 21 Pa s within the lower mantle (from 670 km depth to the core-mantle boundary);-the second model, EM3D_M, adopts the same reference viscosity within the lower mantle, but has higher background viscosity of 𝐴𝐴 5 × 10 20 Pa s in the upper mantle (Figure S1b in Supporting Information S1). The variations in viscosity relative to the assumed reference model are derived by first combining the ANT-20 regional shear-wave seismic velocity model of the upper mantle beneath Antarctica (Lloyd et al, 2020) with the S362ANI global seismic tomography model (Kustowski et al, 2008).…”
Section: Sea-level Modelmentioning
confidence: 99%
“…Two 3-D mantle viscosity structures, which were first constructed in Wan et al (2022), are built upon two different 1-D reference viscosity profiles:-the first model we referred to as EM3D_L, is characterized by a uniform viscosity of 𝐴𝐴 10 20 Pa s in the upper mantle (from the bottom of the lithosphere to the depth of 670 km), and a viscosity value of 𝐴𝐴 5 × 10 21 Pa s within the lower mantle (from 670 km depth to the core-mantle boundary);-the second model, EM3D_M, adopts the same reference viscosity within the lower mantle, but has higher background viscosity of 𝐴𝐴 5 × 10 20 Pa s in the upper mantle (Figure S1b in Supporting Information S1). The variations in viscosity relative to the assumed reference model are derived by first combining the ANT-20 regional shear-wave seismic velocity model of the upper mantle beneath Antarctica (Lloyd et al, 2020) with the S362ANI global seismic tomography model (Kustowski et al, 2008).…”
Section: Sea-level Modelmentioning
confidence: 99%
“…That is, we find the best-fitting linear trend through the last 5 yr of the 1-D viscoelastic-minus-elastic crustal uplift time-series. We performed a set of test calculations using a harmonic truncation level of 1024, and found that while moving to higher resolution did impact the elastic component of the uplift in some areas (see Wan et al 2021 for an in-depth discussion of the resolution dependence of viscoelastic deformation predictions in West Antarctica), our predictions of viscous uplift were negligibly impacted by this change (Fig. S1).…”
Section: Fitting Synthetic Uplift Data With 1-d Viscosity Modelsmentioning
confidence: 97%